IKRAR TALAK DALAM PUTUSAN VERSTEK DAN AKIBAT HUKUMNYA (Studi Analisis Putusan Pengadilan Agama Padang) - rahma, fataqia (Mahkamah : Jurnal Kajian Hukum Islam, 2025)
AbstractThis research was motivated by several verstek decisions in which the wife was not present at the trial and did not send her power of attorney. The problem formulation that the author uses is what the legal consequences of the divorce vow are in the verstek decision. The focus is on two research questions: First, what is the legal status of divorce in the verstek decision in terms of the wife's situation? Second, how to calculate the iddah period in the verstek decision. This research is library research, the primary data in this research was taken from the decision of the Padang Religious Court. In analyzing the data, the author used a research method in the form of content analysis. The results of this research are first, the legal status of the talak that occurred is Sunni because it refers to the Divorce Deed, but the author believes that there is a possibility of talak bid'i because no one knows for sure the condition of the wife other than himself. Second, the wife's iddah is calculated after the divorce vow hearing and the decision has permanent legal force, so the minimum iddah for women is 56 days to 84 days even though the KHI stipulates that the wife's iddah is 90 days. Keywords: Talak, Verstek, Iddah, Sunni, Bid'i. AbstrakPenelitian ini dilatar belakangi beberapa putusan verstek yang mana istri tidak hadir di Persidangan dan tidak mengirim kuasanya. Rumusan masalah yang penulis gunakan adalah bagaiman akibat hukum ikrar talak dalam putusan verstek . Difokuskan dengan dua pertanyan penelitian: Pertama, Bagaimana status hukum talak dalam putusan verstek ditinjau dari keadaan istri . Kedua, Bagaimana menghitung masa iddah dalam putusan verstek . Penelitian ini merupakan penelitian pustaka atau library research, data primer dalam penelitian ini diambil pada putusan Pengadilan Agama Padang. Dalam menganalisis data, penulis menggunakan metode penelitian berupa analisis konten (content analysis). Hasil dari penelitian ini adalah pertama, status hukum talak yang terjadi adalah sunni karena merujuk kepada Akta Cerai, tapi penulis berpendapat adanya kemungkinan talak bid’i karena tidak ada yang tau pasti keadaan istri selain dirinya. Kedua, iddah istri dihitung setelah sidang ikrar talak dan putusan berkekuatan hukum tetap, maka minimal iddah perempuan adalah 56 hari sampai 84 hari walaupun dalam KHI ditetapkan iddah istri selama 90 hari.Kata Kunci: Talak, Verstek, Iddah, Sunni, Bid’i.